PERANCANGAN TOKO TANI INDONESIA CENTER DI KOTA BANJARBARU - Muhammad Najami; Anna Oktaviana; Nurfansyah Nurfansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Toko Tani Indonesia Center (TTIC) is a work program from the Department of Agriculture and Food Security in which several activities are carried out, these activities are in the form of buying and selling food ingredients and distributing cultivation results from TTIC. The problem with Toko Tani Indonesia Center in Banjarbaru City is that there are many changes in the function of the space over time. Changes in the function of this space could become an obstacle in carrying out TTIC activities for some time to come. The use of programming methods that include analysis of actors, activities and their environment to achieve a spatial program that suits the building object and the facade design from the Neo Vernacular concept can be the outer appearance of this building object. It is hoped that the design of Toko Tani Indonesia Center will facilitate the activities of the actors inside and can attract people from the shape of the building's design.